Analisis Yuridis terhadap Penolakan Pernikahan Siri dalam Perkara Isbat Nikah di Wilayah Hukum Pengadilan Agama Bukittinggi Tahun 2024 - Aliffia Puti Deandra; Fajrul WadiWadi (Lembaga Yasin AlSys, 2026)
The rejection of isbat nikah applications for unregistered marriages has received attention in various studies, but research specifically examining the juridical analysis of the rejection of unregistered marriages in isbat nikah cases at the Bukittinggi Religious Court in 2024 remains limited. This study aims to analyze judges’ legal considerations in rejecting isbat nikah applications, examine the rejection based on Islamic law and positive law, and assess its juridical implications for marital status and the civil rights of the parties. This study used a qualitative approach with a juridical case study design, involving judges of the Bukittinggi Religious Court and marriage registrars from the Office of Religious Affairs as informants selected through purposive sampling. Data were collected through interviews and documentation of court decisions, and were then analyzed qualitatively through the stages of data reduction, data display, and conclusion drawing. The results showed that the rejection of isbat nikah applications was based on the non-fulfillment of the pillars and valid requirements of marriage, particularly regarding the invalidity of the marriage guardian, weak witness evidence, and violations of marriage administration. These findings indicate that judges place greater emphasis on legal certainty and substantive legality than on social considerations alone. The conclusion of this study affirms the importance of fulfilling the valid requirements of marriage and registering marriages as a form of legal protection for families. This study contributes to the development of Islamic family law studies, particularly regarding the position of the marriage guardian, witness evidence, and the urgency of marriage registration in isbat nikah cases.